Platinum micromachining using femtosecond laser pulses - Rocha, Luiz Eduardo Raphael da (2023)
Among the many techniques for micromachining, the Direct Laser Writing (DLW) introduces some advantages to the process, such as high resolution, size, and thickness control, while maintaining the materials proprieties after the procedure. The Laser Induced Forward Transfer (LIFT) is a DLW technique, whose principle is to transfer energy from the laser pulse to the sample, ejecting material droplets from the region where the laser beam is focalized. The technique can be performed using ultrashort laser pulses, which leads to nonlinear light-matter interaction, enabling high-resolution depositions and avoiding degradation of the transferred material. A variety of materials can be studied with LIFT, including metals, which draw attention due to its applications. Platinum micromachined structures are used to produce sensors, because of the material stability in different conditions and other applications. In this work, thin films of platinum (Pt) have been used as donor material for fs-LIFT. To characterize the deposition of Pt on glass, optical microscopy and scanning-electron microscope were used. Besides, the influence of the pulse repetition rate, pulse energy, and scanning speed on the produced features was investigated to determine the optimum irradiation parameters, as well as the threshold fluence. The incubation effect, the thickness control by the repetition rate and the production of different structures were studied. The depositions were made using two laser systems, one centered at 800 nm (5 MHz and pulse energy of nJ), and another one centered at 1030 nm (1 to 1000 kHz and pulse energy of μJ). It was observed that the optimum parameters are achieved with energies from 3 to 6 μJ and repetition rate around 1 kHz, as the depositions get homogeneous and well-defined, as well as the possibilities of micromachining tri-dimensional structures and different kind of depositions varying the micromachining conditions.